Dinâmica da inovação no serviço público da atenção primária à saúde - Nodari, Cristine Hermann (My University, 2015)
The theory of innovation has developed intensively in recent decades, including the analysis of innovation in public health. Moreover, the services sector accounts in several countries, including Brazil , annual growth rates in excess of all other sectors of the economy. The Primary Health Care (PHC) is the essence of the reorientation and restructuring of many systems (OPAS, 2005), it acts as a core organizer and integrator of network services and promotion, prevention and rehabilitation of health. Given the importance of the issues guided by the aim to encourage better health in populations from the complex network of APS (MENDES, 2007), and understanding the importance of innovation in services for organizations , the aim of this thesis was to analyze the dynamics of innovation in the public service of APS. Considering the public environment, it was proposed that the APS has a structured logic for the development of innovations from ongoing interactions between different agents in the production of the service. To achieve this central proposition was the need to design holistically development, integration and impact of innovation in the service sector. The methodology used was an exploratory and descriptive divided into two stages of research. The first stage of the research used a semistructured interview to identify the typology of innovation in the industry and understanding of the innovation process. Also, we used a structured questionnaire to analyze the quality of the service under the guidance of APS. The second stage of the survey provided for the use of a structured questionnaire in order to identify the capabilities and preferences mobilized by agents for the occurrence of innovations. Made use of multivariate analysis of the collected data involving qualitative and quantitative techniques considering two steps. The main results show the identification of fifty six innovations related to quality of service under the guidance of APS. Also show a preponderance of server capacity in mobilizing innovation that permits configuring the innovation process in the public service of APS contributing in the design of an evidence – based approach to innovation.
A teoria sobre inovação tem se desenvolvido, intensamente, nas últimas décadas, incluindo a análise da inovação em serviços públicos de saúde. Doravante, o setor de serviços representa em diversos países, inclusive no Brasil, taxas de crescimento anuais superiores a todos os demais setores da economia. A Atenção Primária à Saúde (APS) constitui a essência da reorientação e reestruturação de muitos sistemas de saúde (OPAS, 2005), pois atua como um núcleo organizador e integrador de serviços de rede e de promoção, prevenção e recuperação da saúde. Diante da relevância das questões pautadas pela finalidade de incentivo à melhores condições de saúde nas populações, a partir da rede complexa da APS (MENDES, 2007), e da importância da compreensão da inovação em serviços para as organizações, o objetivo dEsta tese foi analisar a dinâmica das inovações no serviço público da APS. Considerando o ambiente público, propôs – se que a APS possui uma lógica estruturada para o desenvolvimento das inovações a partir de interações constantes entre diferentes agentes na produção do serviço. Para atingirmos essa proposição central, ocorreu a necessidade de conceber, holisticamente, o desenvolvimento, integrações e repercussões da inovação neste setor. A metodologia utilizada foi de uma pesquisa exploratória e descritiva dividida em duas etapas. A primeira etapa da pesquisa utilizou uma entrevista semiestruturada para identificação da tipologia da inovação no setor e entendimento sobre o processo de inovação. Também, utilizou, um questionário estruturado para análise da qualidade do serviço sob orientação da APS. Para a segunda etapa de pesquisa foi aplicado outro questionário estruturado a fim de se identificar as capacidades e preferências mobilizadas pelos agentes para ocorrência de inovações. Fez – se uso de análise multivariada dos dados coletados envolvendo técnicas qualitativas e quantitativas considerando as duas etapas. Os principais resultados apontam para a identificação de cinquenta e seis inovações nas quais estão relacionadas a qualidade do serviço sob orientação da APS. Também, evidenciam uma preponderância da capacidade dos servidores na mobilização das inovações o que permite configurar o processo de inovação no serviço público da APS contribuíndo no delineamento de uma abordagem baseada em evidências para a inovação.
Keywords: Serviços de saúde - Administração; Saúde pública - Brasil; Cuidados primários de saúde - Inovações tecnológicas; Health services administration; Public health - Brazil; Primary health care - Technological innovations